Friday

August 1, 2014

August 1, 2014

Posted by **Jade** on Monday, October 10, 2011 at 9:51pm.

- Calculus -
**Steve**, Tuesday, October 11, 2011 at 12:12amIf f and g are functions of x

d/dx(f/g) = (f'g - fg')/g^2

This is just a variation of the well-loved product rule, where f/g = f * g^-1

d/dx(f * g^-1) = f'*g^-1 + f*(-1)g^-2 * g'

= f'/g - fg'/g^2

= (f'g - fg')/g^2

**Related Questions**

Calculus - f(x)=5+(6/x)+(7/x^2), find f'(x). I haven't done fractions without ...

Calculus - Let f(x)= 5x ------- x–2 are we supposed to use the quotient rule? ...

Calculus - How do I use the chain rule to find the derivative of square root(1-x...

Calculus - y= [(x-3)/(x^2+1)]^2 find the derivative. I know i would start off ...

Calculus - y= [(x-3)/(x^2+1)]^2 I know that I would use the product rule on the ...

calculus - Find the DERIVATIVE: h(x)= e^3x+2/e^3x-2 (quotient rule)

calculus - Differentiate: 1/s+ke^s Do I just use the quotient rule? Thanks

Calculus - Differentiate: y=ln(x/(2x+3))^(1/2) y=(1/2)ln(x/(2x+3)) y'=0+(1/2)((...

calculus - Hey I am working on differentiation/quotient rule for this problem...

Calculus - I'm having problems with this one. Can't get the right answer. ...